Sex-specific differences in the severity of symptoms and recovery rate following sports-related concussion in young athletes - Berz, K.; Divine, J.; Foss, K.; Heyl, R.; Ford, K. R.; Myer, G. D. (The Physician and Sportsmedicine, 2013)
Introduction: While research on adult recovery from concussion indicates sex-specific symptoms and recovery rates, there is little existing data on younger patient populations. Objective: To determine sex-specific differences in the severity of presenting symptoms and recovery rate between groups of young athletes who presented = 7 or > 7 days after sports-related concussion. Methods: This study was a retrospective review of athletes aged 9 to 17 years who were referred for evaluation of a sports-related concussion over a 24-month period. The study groups were divided by sex and post-injury presentation to the clinic at = 7 days and > 7 days from the date of injury. Athletes with learning disabilities were excluded from the study and data analysis. Age, height, and weight were recorded for each subject. Each subject also reported their initial degree of confusion, amnesia, or loss of consciousness, and whether a helmet was worn when the injury was sustained. A 22-item post-concussion symptom score (SS) scale was completed by both groups on initial assessment (SS1) and follow-up visit (SS2). The recovery rate (SSR) was calculated as (SS2-SS1)/days between SS2 and SS1. Sex and group comparisons for SS1 and SSR were performed using 2 × 2 analysis of variance. A similar analysis was also performed for effects of sex on SS1 and SSR in patients who were not wearing a helmet. Results: Thirty-seven athletes aged 15.0 ± 1.9 years were evaluated. Males, regardless of day of presentation, had a lower SS1 evaluation than females (15.8 vs 30.9; P < 0.05). Males without helmets did not differ from females without helmets, but this was not significantly different (14.1 vs 29.6; P = 0.1). There was not a significant difference in SS1 evaluation between the groups who presented at = 7 or > 7 days. The overall mean SSR was -1.2/day, with no significant difference seen between groups or sex. There were no significant differences in degree of loss of consciousness, amnesia, confusion, or age between the sexes or groups. Conclusion: Whether presenting at = 7 or > 7 days following a sports-related concussion, female athletes reported a higher SS1 evaluation. With SSR being similar between sexes, the current data suggest that young, female athletes may take longer to become symptom free following sports-related concussion. This information may be an important factor in returning a young athlete to sport after sports-related concussion.